2016
DOI: 10.1016/j.nmni.2016.03.008
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of toxic shock syndrome toxin–producing epidemic methicillin-resistant Staphylococcus aureus 15 (EMRSA-15) strains in Kuwait hospitals

Abstract: This study characterized EMRSA-15 isolates obtained from patients in Kuwait hospitals for their genotypic relatedness, antibiotic resistance and carriage of virulence genes using pulsed-field gel electrophoresis (PFGE), coagulase serotyping, SCCmec subtyping, spa typing, multilocus sequence typing and DNA microarray. The isolates were resistant to trimethoprim (75.6%), ciprofloxacin (29.7%), erythromycin and clindamycin (24.3%), tetracycline (19.0%), and gentamicin and kanamycin (21.6%). All 37 isolates belong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
41
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 38 publications
12
41
1
Order By: Relevance
“…Toxic shock syndrome toxin 1 (tsst-1), a superantigen secreted by Staph. aureus in susceptible hosts, was responsible for toxic shock syndrome in humans (Kulhankova et al, 2014;Udo et al, 2016;Zarei Koosha et al, 2016). Currently, we found that 40% of Staph.…”
Section: Discussionmentioning
confidence: 76%
“…Toxic shock syndrome toxin 1 (tsst-1), a superantigen secreted by Staph. aureus in susceptible hosts, was responsible for toxic shock syndrome in humans (Kulhankova et al, 2014;Udo et al, 2016;Zarei Koosha et al, 2016). Currently, we found that 40% of Staph.…”
Section: Discussionmentioning
confidence: 76%
“…Secondly, the ST239-III-t860 isolates, obtained only in 2007, did not persist in the Maternity hospital in contrast to their persistence in other hospitals in Kuwait [33, 35]. Most of the ST22-IVa-t223 isolates were obtained from samples of skin and soft tissue infections as well colonization sites as was the case in other hospitals in Kuwait [36] supporting their ability to be involved in different types of infections. In contrast, the UK-EMRSA-15/Barnim epidemic MRSA clone is mostly associated with bloodstream infections [37].…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies reported the local predominance of this clone in many countries including European countries [143,144], the Middle East, Asia, and South America [145]. Another epidemic clone, MRSA-ST22, has been predominately identified in recent years throughout the Middle East [44,45,[146][147][148][149][150][151][152][153][154], Europe [155][156][157][158][159][160], and Asia [161][162][163]. For North Africa, the lower number of studies on MRSA means that MRSA lineages remained unclear.…”
Section: Discussionmentioning
confidence: 99%